(untitled) (Heteroglossia – studia kulturoznawczo-filologiczne, 2019)
The article reviews specific features of the Georgian linguistic world image shaped during the long period of its existence. The analysis covers the cultural concepts and language markers that reflect the national characteristics. Being a special kind of cross-cultural communication, translation is a process of overcoming the linguistic and cultural barriers, and includes transcoding of language code as well as the cultural one. On the one hand, it uncovers the discrepancies between the key concepts in different cultures, and on the other hand, it demonstrates existence of the similar language markers of the ‘global cultural space’ that is being formed.